2015
DOI: 10.1039/c5ta01936b
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazole substituted polymers for high temperature polymer electrolyte fuel cells

Abstract: While tetrazole (TZ) has much lower basicity than imidazole and may not be fully protonated in the presence of phosphoric acid (PA), DFT calculations suggest that the basicity of TZ groups can be increased by the introduction of a 2,6-dioxy-phenyl-group in position 5 of TZ. This structure allows hydrogen bonds between TZ protons and ether oxygen atoms, and thereby establishes a resonance stabilised, co-planar structure for tetrazolium ions. Molecular electrostatic potential (MEP) calculations also indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…This redistribution process does not depend only on MEA material parameters, such as the membrane doping level, 10,11 but is also a function of operation parameters, especially of the current density. Eberhardt et al 12 showed the invasion of the anode gas diffusion layer (GDL) and the anode flow field after increasing the current density for the first time and were confirmed by similar findings by Becker et al, 13,14 and Henkensmeier et al 15 This process of acid redistribution into the anode GDL and flow field channel leads to a loss of phosphoric acid over time. Loss of electrolyte is a major limitation for the lifetime of a HT-PEFC, especially when factoring in the DOE target for combined heat and power applications of 60'000 hours of operation for 2020.…”
mentioning
confidence: 58%
“…This redistribution process does not depend only on MEA material parameters, such as the membrane doping level, 10,11 but is also a function of operation parameters, especially of the current density. Eberhardt et al 12 showed the invasion of the anode gas diffusion layer (GDL) and the anode flow field after increasing the current density for the first time and were confirmed by similar findings by Becker et al, 13,14 and Henkensmeier et al 15 This process of acid redistribution into the anode GDL and flow field channel leads to a loss of phosphoric acid over time. Loss of electrolyte is a major limitation for the lifetime of a HT-PEFC, especially when factoring in the DOE target for combined heat and power applications of 60'000 hours of operation for 2020.…”
mentioning
confidence: 58%
“…In Figure S6, the as-prepared 65 wt % PA-doped co-PI membranes showed higher power density than the conventional sPBI membrane operated at different temperatures [5.5 (30 °C), 6 (80 °C), and 22 mW cm –2 (160 °C)]. Especially, the peak power density of PI-TB-N30C at 160 °C was superior to those of some reported polymers, such as ABPBI (300 mW cm –2 , H 2 /air), OPBI (320 mW cm –2 , H 2 /air), and Tz-poly­(arylene ether) (287 mW cm –2 , H 2 /air), due to the improved proton transmission channel from the high crown ether contents.…”
Section: Resultsmentioning
confidence: 94%
“…The molecular electrostatic potential (MEP) can provide the reactivity sites of electrophilic and nucleophilic attacks. 67,68 The electron-rich and electron-defect regions are labeled by red and blue of compounds 1−3 (see Figure 8). Frontier Molecular Orbital Analysis.…”
Section: ■ Introductionmentioning
confidence: 99%